2019
DOI: 10.1016/j.ygeno.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

pLoc_bal-mGpos: Predict subcellular localization of Gram-positive bacterial proteins by quasi-balancing training dataset and PseAAC

Abstract: Knowledge of protein subcellular localization is vitally important for both basic research and drug development. With the avalanche of protein sequences emerging in the post-genomic age, it is highly desired to develop computational tools for timely and effectively identifying their subcellular localization purely based on the sequence information alone. Recently, a predictor called "pLoc-mGpos" was developed for identifying the subcellular localization of Gram-positive bacterial proteins. Its performance is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 91 publications
0
40
0
Order By: Relevance
“…As pointed out in [124] and demonstrated in a series of recent publications (see, e.g., [40,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144]), user-friendly and publicly accessible web-servers represent the future direction for developing practically more useful prediction methods and computational tools. Actually, many practically useful web-servers have significantly increased the impacts of bioinformatics on medical science [29], driving medicinal chemistry into an unprecedented revolution [96].…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in [124] and demonstrated in a series of recent publications (see, e.g., [40,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144]), user-friendly and publicly accessible web-servers represent the future direction for developing practically more useful prediction methods and computational tools. Actually, many practically useful web-servers have significantly increased the impacts of bioinformatics on medical science [29], driving medicinal chemistry into an unprecedented revolution [96].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that two class problems in the context of supervised machine learning not represented equally in the data set. [52][53][54][55][56][57][58] In binary classification problems, if a data set does not have an equal amount of data from two classes, then the data set is called imbalanced otherwise, it is called balanced. We found that the distribution of two classes present in our data is not uniform between the number of positive instances and negative instances and leads to imbalanced data.…”
Section: Imbalanced Datamentioning
confidence: 99%
“…The web-server is called as "pLoc_bal-mGneg", where "bal" means that the predictor has been treated by balancing or quasi-balancing out the training dataset [3][4][5][6][7][8][9], and "m" means that the predictor is with the capacity to study the multi-label systems. How the web-server is working can be clearly seen via the showcase below.…”
mentioning
confidence: 99%